Bestuurszorg Pemerintah dalam Negara Hukum Indonesia - -, Herman (Esensi Hukum, 2019)
Abstract Bestuurszorg is a concept found in modern rule of law. The main obligations in the rule of law are given duties and functions to the maximum extent to create prosperity and welfare of the people. The preamble to the constitution in force in Indonesia requires the Indonesian government's obligation to create prosperity and welfare. The body (article by article) of this constitution also explicitly states that the State of Indonesia is a state of law based on popular sovereignty. This research is a normative legal research with a statutory approach and a conceptual approach. The results of this study suggest that the obligations of the government in the Indonesian State of Law are duties and functions to create prosperity and welfare of the people. The government is also given the power to implement the constitutions and laws through its authority in terms of making laws and regulations independently. Keywords: State of law, bestuurszorg, prosperity and welfare.